PENGARUH TEMPERATUR REGENERASI TERHADAP PENURUNAN KELEMBABAN RELATIF DAN EFEKTIFITAS PENYERAPAN UAP AIR PADA ALAT UJI DEHUMIDIFIER DENGAN DESICCANT SILICA GEL - . Muchammad (Universitas Wahid Hasyim, 2006)
In industrial field humidity level play an important role on product quality and production process. High humidity can cause a lot of problem. Thus, we need a device or system to reduce air humidity, called dehumidifier. Dehumidifier that used in this experiment is adsorbent dehumidifier which used silica gel as an adsorbent. The aim of the study is to investigate the effect of regeneration temperature on reducing relative humidity at closed room using silica gel desiccant dehumidifier and the effectiveness of desiccant silica gel to adsorb moisture. In this experiment the regeneration temperature variations are 50, 60, 70, 80 and 90 oC the results show that, when regeneration temperature increased, relative humidity in closed room decreased but humidity ratio in the closed room relatively increased. Regeneration temperature at 90 °C could reduce relative humidity down to 40,7 %. In this experiment dehumidification process was not effective because silica gel still too hot after being regenerated. Keyword : moisture, dehumidifier, adsorbent, silica gel